Effects of physical and chemical immobilization on hematologic and biochemical variables in captive brown brocket deer (Mazama gouazoubira) - Munerato, Marina Salles [UNESP]; Barbanti Duarte, Jose Mauricio [UNESP]; Pereira, Gener Tadeu [UNESP]; Marques, Jose Antonio [UNESP] (Amer Soc Veterinary Clinical Pathology, 2010)
BackgroundAlterations in cellular and chemical constituents in blood are indicators of physical or chemical restraint in deer.ObjectivesThe aim of this study was to determine the effects of physical and chemical restraint on hematologic and biochemical analytes in captive brown brocket deer (Mazama gouazoubira).MethodsSix adult deer were physically restrained and randomly anesthetized in a crossover design using 3 protocols (P). In P1, anesthesia was induced directly with isoflurane using a face mask and was maintained with isoflurane delivered by endotracheal tube. In P2, oral premedication with midazolam was followed 1 hour later by induction and maintenance of anesthesia with isoflurane, as in P1. In P3, intravenous anesthesia with a combination of ketamine, xylazine, and atropine was followed by anesthesia with isoflurane, as in P1. Blood was collected immediately after physical restraint (T0) and during anesthesia at 20-minute intervals (T15, T35, and T55). Hematologic and biochemical constituents were determined using manual methods or automated analyzers, with cortisol measured by enzyme immunoassay.ResultsDuring physical restraint, following food and water restriction, significant hemoconcentration, increased WBC count, and lower cortisol concentration were observed compared with results at T15, T35, and T55. During anesthesia, lymphocyte count was lower in P2 than P1, urea concentration was decreased at T15 using P2, and plasma glucose concentration was increased after T0 (P <.01). Among the anesthetic protocols, there was a trend for decreased cortisol concentration using P2.ConclusionsPhysical restraint and anesthesia affect some blood constituents in captive brown brocket deer, and midazolam premedication may modify the intensity of the stress response.
Keywords: Chemical restraint; Cortisol; Hematology; physical restraint; plasma electrolytes; serum chemistry